PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR IPAS TENTANG SISTEM PENCERNAAN MANUSIA DI KELAS V SD INPRES FATUKOA - Oky Wardani Ndiy; Roswita Lioba Nahak; Chintia M.P. Ati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low learning outcomes of students in science subjects, especially the material on the human digestive system in grade V of SD Inpres Fatukoa. This problem is caused by learning that is still centered on the teacher so that students are less active and have difficulty understanding abstract concepts. This study aims to determine the influence of the Project Based Learning (PjBL) learning model on the learning outcomes of IPAS. The method used is a quantitative research with a non-equivalent control group design. The study population was 46 students, consisting of VA class as the experimental class and the VB class as the control class. The data collection technique uses learning outcome tests through pretest and posttest. Data analysis was carried out by normality test, homogeneity test, and independent t-test. The results showed that the average posttest score of the experimental class was 89.29 higher than the control class of 68.23. The results of the hypothesis test showed a significance value of 0.000 < 0.05, which means that there is a significant influence of the use of the PjBL model on student learning outcomes. Thus, it can be concluded that the Project Based Learning learning model is effective in improving the learning outcomes of science in the human digestive system and is able to encourage student activity, creativity, and collaboration in the learning process.